The catalytic reduction of 4-nitrophenol using MoS2/ZnO nanocomposite - Madhushree R; Jadan Resnik Jaleel UC; Dephan Pinheiro; Sunaja Devi KR (Applied Surface Science Advances, 2022)
Nanocomposite MoS2/ZnO was prepared by an exfoliation process and characterized. A flower-like morphology was obtained for the hybrid where uniformly spread ZnO is stacked over thin layers of MoS2. A tight interface between the two components coupled with the energy band bending at the junction has resulted in a high activity of the composite towards the reduction of 4-nitrophenol. A complete reduction to 4-aminophenol from 4-nitrophenol took place within 15 min under the optimized conditions. The catalyst has a recyclability of six times without any perceptible decrease in the catalytic activity.